Anode and secondary battery

By using a combination of silicon-carbon composite material and silicon oxide in the negative electrode active material layer, the particle size ratio and distribution are optimized, and the contradiction between fast charging performance and battery life is solved, and efficient fast charging and long-life batteries are achieved.

JP2025504488AActive Publication Date: 2025-02-12LG ENERGY SOLUTION LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024543248
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-10-12
Filing Date
2023-10-13
Publication Date
2025-02-12
Estimated Expiration
2043-10-13

AI Technical Summary

Technical Problem

The prior art is difficult to improve the service life of the secondary battery while ensuring fast charging performance.

Method used

A two-layer negative electrode active material layer structure is adopted, one of which uses efficient but easily expandable silicon-carbon composite material and the other uses inefficient but long-lived silicon oxide. The position of the negative electrode material is optimized to improve battery performance by controlling the particle size ratio and distribution.

Benefits of technology

While achieving fast charging performance, it significantly improves the service life of the secondary battery and the stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025504488000001
    Figure 2025504488000001
  • Figure 2025504488000002
    Figure 2025504488000002
  • Figure 2025504488000003
    Figure 2025504488000003
Patent Text Reader

Abstract

The present invention relates to a negative electrode for a secondary battery, the negative electrode including the current collector, a first negative electrode active material layer provided on the current collector and containing a silicon carbon composite, and a second negative electrode active material layer provided on the first negative electrode active material layer and containing a silicon oxide, and a secondary battery including the same.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of the filing date of Korean Patent Application No. 10-2022-0132114 filed with the Korean Intellectual Property Office on October 14, 2022, and Korean Patent Application No. 10-2023-0135780 filed with the Korean Intellectual Property Office on October 12, 2023, the entire contents of which are incorporated herein by reference.

[0002] The present invention relates to a negative electrode for a secondary battery and a secondary battery including the same. [Background technology]

[0003] Secondary batteries are widely used not only in portable devices but also in electric vehicles (EVs, Electric Vehicles) and hybrid electric vehicles (HEVs, Hybrid Electric Vehicles) that are powered by electrical sources.

[0004] Such secondary batteries have the primary advantage of dramatically reducing the use of fossil fuels, as well as the advantage of not producing any by-products from the use of energy, and are therefore attracting attention as a new energy source that is environmentally friendly and can improve energy efficiency.

[0005] In general, a secondary battery includes a positive electrode, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, etc. In addition, the electrodes such as the positive electrode and the negative electrode may have an electrode active material layer provided on a current collector.

[0006] As the use of secondary batteries increases, various battery performances are required. In order to improve battery performance, attempts have been made to appropriately compose the electrode active material layer, but while some battery performances may be improved depending on the selection or combination of materials, other performances may be deteriorated. Therefore, research is required to select or combine appropriate materials depending on the performance of the secondary battery to be improved. Summary of the Invention [Problem to be solved by the invention]

[0007] An object of the present invention is to provide a negative electrode capable of providing a secondary battery having rapid charging performance and improved life span, and a secondary battery including the same. [Means for solving the problem]

[0008] One embodiment of the present invention comprises: Current collector; a first negative electrode active material layer disposed on the current collector and including a silicon carbon composite; and a second negative electrode active material layer including silicon oxide provided on the first negative electrode active material layer; Including, The average particle size (D 50,1st ) to the average particle size (D 50,2nd ) ratio (D 50,2nd / D 50,1st ) provides a negative electrode for a secondary battery in which the ratio is 0.75 to 1.5.

[0009] Another embodiment of the present invention provides a secondary battery comprising the above-mentioned negative electrode for secondary batteries, a positive electrode, and a separator. Effect of the Invention

[0010] According to the embodiments described herein, a secondary battery having excellent rapid charging performance and improved life span can be provided by disposing a silicon-carbon composite and a silicon oxide, which are silicon-based active materials with different efficiency and swelling characteristics, at specific positions in a two-layer negative electrode active material layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The present invention will be described in more detail below to help the understanding of the present invention. The present invention can be embodied in various different forms and is not limited to the embodiments described herein. In this regard, the terms or words used in the present specification and claims are not to be construed as being limited to their ordinary or dictionary meanings, but are to be construed as having meanings and concepts that correspond to the technical ideas of the present invention, based on the principle that the inventor can appropriately define the concepts of terms in order to best describe his / her invention.

[0012] As used herein, terms such as "comprise", "comprise", or "have" are intended to specify the presence of embodied features, numbers, steps, components, or combinations thereof, and are understood as not precluding the possibility of the presence or addition of one or more other features, numbers, steps, components, or combinations thereof.

[0013] Furthermore, when a part such as a layer is said to be "above" another part, this does not only mean that it is "directly above" the other part, but also includes cases where there is another part between them. Conversely, when a part is said to be "directly above" another part, it means that there is no other part between them. Note that being "above" a reference part refers to being located above or below the reference part, and does not necessarily mean being located "above" in the opposite direction of gravity.

[0014] In this specification, a description referring only to an "active material layer" without the terms "first" and "second" can apply to both the first and second active material layers.

[0015] According to one embodiment of the present specification, there is provided a negative electrode for a secondary battery, comprising: a current collector; a first negative electrode active material layer provided on the current collector and including a silicon carbon composite; and a second negative electrode active material layer provided on the first negative electrode active material layer and including a silicon oxide, The average particle size (D 50,1st ) relative to the average particle size (D50,2nd ) ratio (D 50,2nd / D 50,1st ) is 0.75 to 1.5.

[0016] In recent years, in order to improve the rapid charging, which is the most important requirement for automobile batteries, attempts have been made to design batteries by arranging silicon-based active materials in the negative electrode. However, the present inventors have found that if a silicon-based active material with large swelling is arranged in the upper layer of the negative electrode, the upper layer is used intensively during charging and discharging, and the silicon-based active material present in the upper layer is concentrated and degenerated, resulting in poor life characteristics. Therefore, the present inventors have clarified that by using two types of silicon-based active materials with different efficiency and swelling characteristics and arranging them at specific positions in two negative electrode active material layers, a battery with excellent rapid charging and improved life characteristics can be provided, and have arrived at the present invention.

[0017] Specifically, the negative electrode for a secondary battery according to the embodiment is characterized in that, among silicon-based active materials, a silicon carbon composite is contained in a first negative electrode active material layer disposed adjacent to a current collector, and a silicon oxide is contained in a second negative electrode active material layer disposed away from the current collector. Since silicon oxide has a relatively low efficiency but a long life characteristic, and a silicon carbon composite has a high efficiency characteristic, by disposing the silicon oxide and the silicon carbon composite in the upper and lower layers of the two negative electrode active material layers, respectively, it is possible to improve the life characteristic while maintaining excellent fast charging performance.

[0018] In addition, the average particle size (D 50,1st ) relative to the average particle size (D 50,2nd ) ratio ( D50,2nd / D 50,1st ) may be 0.75 to 1.5, or 0.9 to 1.1, or 0.9 to 1.

[0019] If the average particle size of the silicon carbon composite contained in the first negative electrode active material layer and the average particle size of the silicon oxide contained in the second negative electrode active material layer are out of the above range, the pore structures will be heterogeneous, which may hinder the mobility of lithium ions and cause a difference in reactivity between the first negative electrode active material layer and the second negative electrode active material layer, which may adversely affect the battery life.

[0020] According to one embodiment, the silicon carbon composite contained in the first negative electrode active material layer has a discharge efficiency of 85% to 95%, and the silicon oxide contained in the second negative electrode active material layer has a discharge efficiency of 75% to 85%.

[0021] The discharge efficiency of the negative active material can be measured as follows.

[0022] First, the negative electrode active material, Super-C (registered trademark) conductive material, carboxymethyl cellulose (CMC) thickener, and styrene-butadiene rubber (SBR) binder polymer were added to water in a weight ratio of 95:1:1:3 to prepare a negative electrode slurry. The negative electrode slurry was then coated on a copper foil to form a 1.4875 cm 2 The resultant is punched out to have an area of ​​100 mm, rolled, and then dried to produce a negative electrode. An electrode assembly is produced by using lithium metal as a counter electrode together with the negative electrode through a polypropylene separator. A non-aqueous electrolyte is produced by adding 1M LiPF6 to an organic solvent in which ethylene carbonate and ethyl methyl carbonate are mixed in a volume ratio of 3:7 and vinylene carbonate is added to make a concentration of 1 wt %, and then pouring the electrolyte into the electrode assembly to produce a coin-type semi-secondary battery (CHC; coin half cell).

[0023] When charging the negative electrode coin-type semi-secondary battery (CHC) fabricated as described above, a constant current is applied at a rate of 0.2C in a CC-CV (constant current constant voltage) manner up to 0.005V, and then the current is controlled at a constant voltage of 0.005V. When discharging, it is cut off at 1.5V in a CC (constant current) manner at a rate of 0.2C, and the discharge efficiency can be measured. The discharge efficiency can be calculated as discharge capacity / charge capacity × 100.

[0024] In this specification, the silicon-carbon composite is a composite of Si and C, and may be represented as a Si / C-based active material, which is distinguished from silicon carbide (Silicon carbide) denoted as SiC. The silicon-carbon composite may be a composite of silicon and graphite, etc., and may also form a structure in which a core in which silicon and graphite, etc. are composite is surrounded by graphene or amorphous carbon, etc. In the silicon-carbon composite, the silicon may be nano-silicon.

[0025] In this specification, the silicon oxide may be represented by SiO x (0 < x < 2). The silicon oxide may be silicon-based composite particles containing SiO x (0 < x < 2) and pores.

[0026] The SiO x (0 < x < 2) corresponds to the matrix within the silicon-based composite particles. The SiO x (0 < x < 2) may be in a form containing Si and SiO2, and the Si may form a phase. That is, the x corresponds to the number ratio of O to Si contained in the SiO x (0 < x < 2). When the silicon-based composite particles contain the SiO x (0 < x < 2), the discharge capacity of the secondary battery can be improved.

[0027] The silicon-based composite particles may further contain at least one of a magnesium (Mg) compound and a lithium (Li) compound. The magnesium (Mg) compound and the lithium (Li) compound can correspond to a matrix within the silicon-based composite particles.

[0028] The magnesium (Mg) compound and / or the lithium (Li) compound may be present inside and / or on the surface of the SiO x (0 < x < 2). The initial efficiency of the battery can be improved by the magnesium (Mg) compound and / or the lithium (Li) compound.

[0029] The magnesium (Mg) compound may contain at least one selected from the group consisting of magnesium (Mg) silicate, magnesium (Mg) silicide, and magnesium (Mg) oxide. The magnesium (Mg) silicate may contain at least one of Mg2SiO4 and MgSiO3. The magnesium (Mg) silicide may contain Mg2Si. The magnesium (Mg) oxide may contain MgO.

[0030] In one embodiment of the present specification, the magnesium (Mg) element may be contained in an amount of 0.1 wt% to 20 wt%, or 0.1 wt% to 10 wt%, based on 100 wt% of the total silicon-based active material. Specifically, the magnesium (Mg) element may be contained in an amount of 0.5 wt% to 8 wt% or 0.8 wt% to 4 wt%. When the above range is satisfied, the magnesium (Mg) compound can be contained in an appropriate amount within the silicon-based active material, so that the volume change of the silicon-based active material can be easily suppressed during charging and discharging of the battery, and the discharge capacity and initial efficiency of the battery can be improved.

[0031] The lithium (Li) compound may include at least one selected from the group consisting of lithium (Li) silicate, lithium (Li) silicide, and lithium (Li) oxide. The lithium (Li) silicate may include at least one of Li2SiO3, Li4SiO4, and Li2Si2O5. The lithium (Li) silicide may include Li7Si2. The lithium (Li) oxide may include Li2O.

[0032] In one embodiment of the present invention, the lithium (Li) compound may include a form of lithium silicate. The lithium silicate is represented by Li a Si b O c (2 ≤ a ≤ 4, 0 < b ≤ 2, 2 ≤ c ≤ 5), and can be classified into crystalline lithium silicate and amorphous lithium silicate. The crystalline lithium silicate can exist in the form of at least one lithium silicate selected from the group consisting of Li2SiO3, Li4SiO4, and Li2Si2O5 within the silicon-based composite particles, and the amorphous lithium silicate may be in the form of Li a Si b O c (2 ≤ a ≤ 4, 0 < b ≤ 2, 2 ≤ c ≤ 5), and is not limited to the above form.

[0033] In one embodiment of the present specification, the lithium (Li) element may be contained in an amount of 0.1 wt% to 20 wt%, or may be contained in an amount of 0.1 wt% to 10 wt% based on 100 wt% of the total silicon-based active material. Specifically, the lithium (Li) element may be contained in an amount of 0.5 wt% to 8 wt%, and more specifically, may be contained in an amount of 0.5 wt% to 4 wt%. When the above range is satisfied, the lithium (Li) compound can be contained in an appropriate content within the silicon-based active material, so that the change in the volume of the negative electrode active material can be easily suppressed during charging and discharging of the battery, and the discharge capacity and initial efficiency of the battery can be improved.

[0034] The content of the Mg element or lithium (Li) element can be confirmed by ICP (capacitively coupled plasma) analysis. For the ICP analysis, a certain amount (about 0.01 g) of the negative active material is accurately taken and then transferred to a platinum crucible, and nitric acid, hydrofluoric acid, and sulfuric acid are added and completely decomposed on a hot plate. Then, an inductively coupled plasma emission spectroscope (ICPAES, Perkin-Elmer 7300) is used to measure the intensity of a standard solution prepared using a standard solution (5 mg / kg) at a wavelength specific to magnesium (Mg) element or lithium (Li) element to create a reference calibration curve. Then, the pretreated sample solution and the base sample are introduced into the instrument, and the intensity of each is measured to calculate the actual intensity, and the concentration of each component is calculated relative to the created calibration curve, and the magnesium (Mg) element or lithium (Li) element content of the silicon-based active material manufactured can be analyzed by converting the total sum to a theoretical value.

[0035] In one embodiment of the present specification, a carbon layer may be provided on the surface and / or inside the pores of the silicon-based composite particles. The carbon layer imparts electrical conductivity to the silicon-based composite particles, and the initial efficiency, life characteristics, and battery capacity characteristics of a secondary battery including a negative electrode active material including the silicon-based composite particles may be improved. The total weight of the carbon layer may be 5% by weight to 40% by weight based on a total of 100% by weight of the silicon-based composite particles.

[0036] In one embodiment of the present specification, the carbon layer may include at least one of amorphous carbon and crystalline carbon.

[0037] The average particle size (D 50 ) may be 2 μm to 15 μm, specifically 3 μm to 12 μm, and more specifically 4 μm to 10 μm. When the above range is satisfied, side reactions between the silicon-based composite particles and the electrolyte are controlled, and the discharge capacity and initial efficiency of the battery can be effectively realized.

[0038] In this specification, the average particle size (D 50The average particle size (D) can be defined as the particle size that corresponds to 50% of the cumulative volume in the particle size distribution curve. 50 ) can be measured, for example, by the laser diffraction method. The laser diffraction method generally allows measurement of particle sizes from the submicron range to about several mm, and can provide results with high reproducibility and high resolution.

[0039] According to one embodiment, the silicon carbon composite in the first negative electrode active material layer may be included in an amount of 1 wt% to 20 wt% based on 100 wt% of the first negative electrode active material layer, and the silicon oxide in the second negative electrode active material layer may be included in an amount of 1 wt% to 20 wt% based on 100 wt% of the second negative electrode active material layer. When the content of the silicon carbon composite or silicon oxide in the first and second negative electrode active material layers is 1 wt% or more, the capacity gain becomes more than a certain level, and the advantage of using the material can be realized, and when the content is 20 wt% or less, excessive swelling is prevented, which is advantageous for the life and battery characteristics, and is also price competitive in terms of cost.

[0040] According to one embodiment, the first negative electrode active material layer and the second negative electrode active material layer further include a carbon-based active material. The carbon-based active material may be graphite, and the graphite may be natural graphite, artificial graphite, or a mixture thereof. The carbon-based active material may be included in an amount of 80 parts by weight to 99 parts by weight based on 100 parts by weight of the total negative electrode active material included in each negative electrode active material layer.

[0041] In one embodiment of the present specification, the negative electrode active material in 100 parts by weight of each negative electrode active material layer may be contained in an amount of 80 parts by weight or more and 99.9 parts by weight or less, preferably 90 parts by weight or more and 99.9 parts by weight or less, more preferably 95 parts by weight or more and 99.9 parts by weight or less, and still more preferably 98 parts by weight or more and 99.9 parts by weight or less.

[0042] According to a further embodiment of the present specification, the negative electrode active material layer may further include a negative electrode binder in addition to the silicon-based active material and the carbon-based active material.

[0043] The negative electrode binder may play a role in improving the adhesion between the negative electrode active material particles and the adhesive strength between the negative electrode active material particles and the negative electrode current collector. The negative electrode binder may be any one known in the art, and non-limiting examples thereof include at least one selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethylmethacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid, and substances in which hydrogen is substituted with Li, Na, Ca, or the like, or various copolymers thereof.

[0044] The negative electrode binder may be included in an amount of 0.1 parts by weight to 20 parts by weight, for example, preferably 0.3 parts by weight to 20 parts by weight, and more preferably 0.5 parts by weight to 10 parts by weight, based on 100 parts by weight of the negative electrode active material layer.

[0045] The negative electrode active material layer may not include a conductive material, but may further include a conductive material if necessary. The conductive material included in the negative electrode active material layer is not particularly limited as long as it does not induce a chemical change in the battery and has conductivity, and examples thereof include graphite such as natural graphite and artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; conductive tubes such as carbon nanotubes; metal powders such as fluorocarbon, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives. The content of the conductive material in the negative electrode active material layer may be 0.01 parts by weight to 20 parts by weight, preferably 0.03 parts by weight to 18 parts by weight, based on 100 parts by weight of the negative electrode active material layer.

[0046] In one embodiment of the present specification, the first and second negative electrode active material layers may each have a thickness of 10 μm or more and 150 μm or less. The weight loading of the first and second negative electrode active material layers may each be 50 to 300 mg / 25 cm. 2 Weight loading is weight based on dry solids.

[0047] In one embodiment of the present specification, the negative electrode current collector is not particularly limited as long as it is conductive and does not induce chemical changes in the battery. For example, the current collector can be made of copper, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, or the like. Specifically, transition metals that adsorb carbon well, such as copper and nickel, can be used as the current collector. The thickness of the current collector can be 1 μm to 500 μm, but the thickness of the current collector is not limited thereto.

[0048] A further embodiment herein provides a secondary battery comprising an anode, a cathode and a separator according to the previous embodiment.

[0049] In one embodiment of the present specification, the positive electrode includes a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector and including the positive electrode active material. The positive electrode active material layer may have a thickness of 20 μm or more and 500 μm or less.

[0050] The positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity, and for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. can be used. The positive electrode current collector may usually have a thickness of 1 to 500 μm, and fine irregularities can be formed on the collector surface to increase the adhesive strength of the positive electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0051] In one embodiment of the present specification, the positive electrode may include a lithium composite transition metal compound including nickel (Ni) and cobalt (Co) as an active material. The lithium composite transition metal compound may further include at least one of manganese and aluminum. The lithium composite transition metal compound may include nickel in an amount of 80 mol % or more, for example, 80 mol % or more and less than 100 mol %, of metals other than lithium.

[0052] In one embodiment, the positive electrode active material in 100 parts by weight of the positive electrode active material layer may be contained in an amount of 80 parts by weight or more and 99.9 parts by weight or less, preferably 90 parts by weight or more and 99.9 parts by weight or less, more preferably 95 parts by weight or more and 99.9 parts by weight or less, and even more preferably 98 parts by weight or more and 99.9 parts by weight or less.

[0053] According to a further embodiment of the present specification, the positive electrode active material layer according to the above embodiment may further include a positive electrode binder and a conductive material.

[0054] The positive electrode binder may play a role in improving the adhesion between the positive electrode active material particles and the adhesive strength between the positive electrode active material particles and the positive electrode current collector. As the positive electrode binder, those known in the art may be used, and non-limiting examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, or various copolymers thereof, and one or more of these may be used alone or in combination.

[0055] The positive electrode binder may be included in an amount of 0.1 parts by weight to 50 parts by weight, for example, preferably 0.3 parts by weight to 35 parts by weight, and more preferably 0.5 parts by weight to 20 parts by weight, based on 100 parts by weight of the positive electrode active material layer.

[0056] The conductive material contained in the positive electrode active material layer is used to impart conductivity to the electrode, and can be used without any particular limitation as long as it does not undergo chemical changes in the battery and has electronic conductivity.Specific examples include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fibers; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and the like, and one or more of these may be used alone or in mixture.

[0057] Specifically, in one embodiment, the conductive material may include one or more of single-walled carbon nanotubes (SWCNTs) and multi-walled carbon nanotubes (MWCNTs). The conductive material may be included in an amount of 0.1 parts by weight or more and 2 parts by weight or less based on 100 parts by weight of the composition for the positive electrode active material layer, for example, preferably 0.3 parts by weight or more and 1.5 parts by weight or less, more preferably 0.5 parts by weight or more and 1.2 parts by weight or less.

[0058] The positive and negative electrodes may be manufactured according to a typical method for manufacturing a positive and negative electrode, except for using the positive and negative active materials. Specifically, the active material layer forming composition containing the active material and, optionally, a binder and a conductive material may be applied to a current collector, followed by drying and rolling. In this case, the types and contents of the positive and negative active materials, binder, and conductive material are as described above. The solvent may be a solvent commonly used in the art, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, or water, and one or more of these may be used alone or in combination. The amount of the solvent used is sufficient to dissolve or disperse the active material, conductive material, and binder in consideration of the coating thickness of the slurry and the manufacturing yield, and to have a viscosity that can provide excellent thickness uniformity when applied to manufacture the positive and negative electrodes. As another method, the positive electrode and the negative electrode may be produced by casting the active material layer forming composition on a separate support, peeling the composition off from the support, and laminating the resulting film on a current collector.

[0059] The separator separates the negative electrode and the positive electrode and provides a passage for lithium ions to move. Any separator generally used in secondary batteries can be used without any particular limitation. In particular, it is preferable that the separator has low resistance to the ion movement of the electrolyte and excellent electrolyte humidification ability. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof may be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of high-melting glass fiber, polyethylene terephthalate fiber, etc. may be used. In addition, a coated separator containing a ceramic component or a polymeric material may be used to ensure heat resistance or mechanical strength, and may be selectively used in a single layer or multilayer structure.

[0060] Examples of the electrolyte include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the manufacture of lithium secondary batteries, but are not limited to these.

[0061] Specifically, the electrolyte may include a non-aqueous organic solvent and a metal salt.

[0062] Examples of the non-aqueous organic solvent include aprotic organic solvents such as N-methyl-2-pyrrolidinone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, gamma-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, phosphoric acid triester, trimethoxymethane, dioxolane derivatives, sulfolane, methylsulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate.

[0063] In particular, ethylene carbonate and propylene carbonate, which are cyclic carbonates among the carbonate-based organic solvents, are preferably used because they are high-viscosity organic solvents with high dielectric constants and good dissociation of lithium salts. When such cyclic carbonates are mixed with linear carbonates having low viscosity and low dielectric constants, such as dimethyl carbonate and diethyl carbonate, in an appropriate ratio, an electrolyte having high electrical conductivity can be produced, and therefore these can be used more preferably.

[0064] The metal salt may be a lithium salt, which is a substance that is easily dissolved in the non-aqueous electrolyte. For example, the anion of the lithium salt may be F - , Cl - , I - , NO3 - , N(CN)2 - , BF4 - , ClO4 - , PF6 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF - , (CF3)6P - , CF3SO3 - , CF3CF2SO3- , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - and (CF3CF2SO2)2N - One or more selected from the group consisting of:

[0065] In addition to the electrolyte components, the electrolyte may further include one or more additives such as haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, and aluminum trichloride for the purpose of improving the life characteristics of the battery, suppressing a decrease in battery capacity, and improving the discharge capacity of the battery.

[0066] A secondary battery according to one embodiment of the present invention includes an assembly including a positive electrode, a negative electrode, a separator and an electrolyte, which may be a lithium secondary battery.

[0067] A further embodiment of the present invention provides a battery module including the above-mentioned secondary battery as a unit cell, and a battery pack including the same. The battery module and the battery pack include the secondary battery having high capacity, high rate-limiting characteristics and high cycle characteristics, and therefore can be used as a power source for a medium- to large-sized device selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems.

[0068] The secondary battery according to the embodiment of the present invention stably exhibits excellent discharge capacity, output characteristics, and cycle performance, and can be used as a power source for medium- to large-sized devices selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems, as well as portable devices such as mobile phones, notebook computers, and digital cameras. For example, the battery module or battery pack can be used as a power source for one or more medium- to large-sized devices including power tools, electric vehicles (EVs), hybrid electric vehicles, and plug-in hybrid electric vehicles (PHEVs), or power storage systems.

[0069] In the following, preferred embodiments are presented to aid in understanding the present invention, but the embodiments are merely illustrative of the present invention, and it is obvious to those skilled in the art that various changes and modifications are possible within the scope of the scope and technical ideas of the present invention. Such changes and modifications are naturally within the scope of the accompanying claims.

[0070] Example 1 A silicon carbon composite (with a discharge efficiency of 90%, D 50 A composition for forming a first negative electrode active material layer containing a negative electrode active material (containing 5 parts by weight of silicon carbon composite based on 100 parts by weight of the negative electrode active material) containing a carbon-based active material (including artificial graphite and natural graphite), a conductive material (including carbon black and CNT), a binder (SBR) and a thickener (CMC) in a weight ratio of 95.9:1.0:2.0:1.1 was coated to a dry thickness of 70 μm and then dried to form a first negative electrode active material layer. Next, SiO (D 50A second negative electrode active material layer-forming composition including a negative electrode active material (SiO content: 5 parts by weight based on 100 parts by weight of the negative electrode active material) including a carbon-based active material (including artificial graphite and natural graphite), a conductive material (including carbon black and CNT), a binder (SBR) and a thickener (CMC) in a weight ratio of 94.9:1.0:3.0:1.1 was coated on the first negative electrode active material layer to a thickness of 70 μm in a dry state and then dried to form a second negative electrode active material layer, thereby preparing a negative electrode.

[0071] Li 1.0 Ni 0.84 Co 0.08 Mn 0.08 A positive electrode active material layer-forming composition containing lithium nickel-based oxide particles of O2, a conductive material (CNT), and a binder (PVDF) in a weight ratio of 97:1:2 was coated onto an aluminum foil having a thickness of 15 μm to a dry thickness of 130 μm, and then dried to produce a positive electrode.

[0072] The positive and negative electrodes were laminated with a separator in between, and an electrolyte was injected to prepare a battery. The electrolyte contained 1M LiPF6, ethylene carbonate (EC) / ethyl methyl carbonate (EMC) (volume ratio 3 / 7), and vinylene carbonate (VC) / propane sultone (PS) (3 parts by weight and 1.5 parts by weight, respectively, based on 100 parts by weight of the electrolyte).

[0073] In order to confirm the rapid charging life performance of the prepared battery, it was cycled by charging at 2.0 C to 4.1 V at room temperature (25°C) and discharging at 0.33 C constant current (CC) (cut at 2.5 V). The capacity retention rate after 100 cycles is shown in Table 1 below.

[0074] Comparative Example 1 The same procedure as in Example 1 was carried out, except that the first negative electrode active material layer contained SiO instead of the silicon carbon composite.

[0075] [Table 1]

[0076] As shown in Table 1, the capacity retention rate of the Examples was significantly higher than that of the Comparative Examples, and this confirmed that the Examples had excellent rapid charging life performance.

Claims

1. Current collector, a first negative electrode active material layer provided on the current collector and including a silicon carbon composite; and a second negative electrode active material layer including silicon oxide provided on the first negative electrode active material layer; Including, The average particle size (D 50,1st ) relative to the average particle diameter (D 50,2nd ) ratio (D 50,2nd / D 50,1st ) is 0.75 to 1.

5.

2. 2. The negative electrode of claim 1, wherein the silicon carbon composite contained in the first negative electrode active material layer has a discharge efficiency of 85% to 95%.

3. 2. The negative electrode of claim 1, wherein the silicon oxide contained in the second negative electrode active material layer has a discharge efficiency of 75% to 85%.

4. The average particle size (D 50 , 1st ) relative to the average particle diameter (D 50 , 2nd ) ratio (D 50,2nd / D 50,1st 2. The negative electrode for secondary batteries according to claim 1, wherein the ratio of the number of ions to the number of carbon atoms is 0.9 to 1.

5. The negative electrode for a secondary battery according to claim 1 , wherein the first negative electrode active material layer and the second negative electrode active material layer further contain a carbon-based active material.

6. The negative electrode for a secondary battery according to claim 5 , wherein the carbon-based active material includes at least one of artificial graphite and natural graphite.

7. 2. The negative electrode for a secondary battery according to claim 1, wherein the silicon carbon composite in the first negative electrode active material layer is contained in an amount of 1 wt % to 20 wt % based on 100 wt % of the first negative electrode active material layer, and the silicon oxide in the second negative electrode active material layer is contained in an amount of 1 wt % to 20 wt % based on 100 wt % of the second negative electrode active material layer.

8. 2. The negative electrode for a secondary battery according to claim 1, wherein the first negative electrode active material layer and the second negative electrode active material layer each have a thickness of 10 μm to 150 μm.

9. A secondary battery comprising the negative electrode for a secondary battery according to claim 1 , a positive electrode, and a separator.

10. The secondary battery according to claim 9 , wherein the positive electrode contains a lithium composite transition metal compound containing nickel (Ni) and cobalt (Co) as an active material.

11. The secondary battery according to claim 10 , wherein the lithium transition metal composite compound further contains at least one of manganese (Mn) and aluminum (Al).

Citation Information

Patent Citations

  • Negative electrode plate, electrochemical device, and electronic device

    EP3886218A1

  • METHOD OF MANUFACTURING Si / C COMPLEX TYPE NEGATIVE ELECTRODE ACTIVE MATERIAL

    JP2009277485A

  • Negative electrode for lithium secondary battery, and lithium secondary battery

    JP2015232921A

  • Electrode for nonaqueous electrolyte battery, nonaqueous electrolyte secondary battery, and battery pack

    JP2016181487A

  • Secondary battery, its manufacturing method and device equipped with the secondary battery

    JP2022527147A